FACTORS WHICH AFFECT ON TREATMENT, REHABILITATION AND RECURRENCE OF DEPRESSION IN PATIENTS - Sakharuk, L. Yu. (Rehabilitation and Recreation, 2022)
Depressive disorders lead to severe medical and social consequences. There are a large number of factors of the external and internal environment of a person which provoke the development of depression, affect on the duration of remission, and are the triggers of repeated depressive episodes. The purpose of the study is identification of the dominant provoking factors of the development of depression, analyzing correlations between them and the term of remission and anamnestic data. The research materials were data from 67 medical histories and charts of outpatients with recurrent depressive disorder who were referred for inpatient treatment. As a result of the research, it was established that the duration of the remission period is 97.9 days on average (δ – 20.5; m – 2.5; min – 61 days, max – 128 days). In 19.4% of cases, the presence of chronic somatic disorders and their long-term treatment contributed to the exacerbation of depression. No linear correlation was found between the age of patients with depression and the duration of the remission period. A certain interdependence was established between the duration of the remission period and the aggravating factor of depression – a weak positive correlation between a stressful event (r=0.11), the death of a loved one (r=0.14); weak inverse correlation between the presence of chronic somatic disorders (r=-0.22), the presence of other mental disorders (r=-0.16), the change of seasons in the year (r=-016). Cross-directional correlations between anamnestic data of patients and factors in the development of depressive disorders are also highlighted. Accordingly, a significant positive correlation was found between burdensome family history and alcohol abuse, taking narcotics, psychoactive substances (r=0.53); inverse weak correlation – between burdensome family history and the presence of chronic somatic diseases (r=-0.23). So, the conducted analysis indicates the need to take into account the factors that provoke the development of depression when drawing up an individual treatment and rehabilitation program and when carrying out preventive measures to extend the period of remission.